Assessment of the Toxicity of Free and PLGA-Encapsulated Phospholipase A2 CB: An In Vitro Approach - Gonçalves, Vanessa Barbosa Pinheiro; de Moura, Gabriel Acácio; Viana Rodrigues, João Pedro; Latorre, Javier Martinez; Candela-Nogueira, Vicente; Soriano-Teruel, Paula M.; Fernandez, Alba Garcia; Máñez, Ramón Martínez; de Medeiros Chaves, Marlos; do Ó Pessoa, Claudia; de Lima, Anderson Maciel; Soares, Andreimar Martins; et al. (Current Medicinal Chemistry, 2025)
BackgroundThe use of bioactive molecules isolated from rattlesnake venom and other poisons has been ongoing for years. Among these bioactive compounds present in snake venom, crotoxin (CTX) stands out as a β-heterodimeric neurotoxin isolated from the venom of Crotalus durissus terrificus. Research on this toxin for its applicability to tumor inhibition has advanced to clinical trials in recent years. Consequently, concerns regarding the use of a toxin as a treatment and the search for dose control that does not trigger extreme toxicity have emerged. Thus, it is necessary to investigate alternatives for controlled delivery and targeted toxin administration.MethodsThis study aimed to evaluate the in vitro toxic action of CTX and its phospholipase A2 CB (PLA2CB) component, both free and encapsulated in polymeric nanoparticles. The inhibitory concentration value of 50% tumor growth (IC50) for CTX and PLA2CB was determined in an initial screening against six tumor cell lines. After identifying the lowest inhibitory concentration value of 0.8 μM observed in human melanoma (SK-MEL-103), this cell line was chosen.ResultsThe cell death mechanism triggered by CTX and PLA2CB exhibited characteristics associated with the necrotic process. However, polymeric nanoparticles containing PLA2CB (NP-PLA2CB) demonstrated apoptosis-like cell death processes in flow cytometry. PLGA polymeric nanoparticles containing PLA2CB were synthesized using microfluidics, resulting in NP-PLA2CB with a diameter of 91 ± 2.9 nm and a zeta potential of -21.8 ± 3.2 mV. The encapsulation efficiency of PLA2CB was approximately 70% (protein content).ConclusionIt was concluded that using the phospholipase component of the toxin in a polymeric-controlled delivery and targeted system may be an alternative solution to the issues in advancing this bioactive molecule in clinical-oncological studies. However, further studies are still being conducted for targeted treatment involving this nanotechnological approach.
Keywords: polymeric nanoparticles